ROLE OF EDUCATION IN EMPOWERING WOMEN: A MULTIDIMENSIONAL ANALYSIS ACROSS SOCIO-ECONOMIC CONTEXTS IN INDIA - Hemamalini Bv (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Education is one of the fundamentals of women empowerment since it is thought to have a transformative power that could liberate women from socio-economic obstacle and also enable them to participate in the development of society. In a country like India which is often divided by deep gender disparities between urban and rural societies, education helps make women economically independent, socially mobile, health conscious, and politically empowered. Abstract This empirical paper critically examines the potential benefits of education to women across different socio-economic strata in India in multiple dimensions—in terms of economic capacity, social status, health and engagement with political process. Drawing on policy discourses and qualitative evidence, the paper identifies a classroom learning space in which education plays a role in enabling women-to-girls to learn to challenge systemic inequalities and patriarchal practices. Whilst there has been considerable headway in increasing female literacy, there are still challenges, such as poverty, social discrimination and states of infrastructure, which restrict girls from attending school also taking the race forward on education, particularly in the marginalized communities. Conclusions The results highlight the importance of targeted educational interventions, such as vocational training programs, sex specific curricula and the proper implementation of policies to support gender disparity and fully mobilize the potential of education as a vehicle for empowerment. This paper provides a set of policy recommendations that can be used by policymakers and other stakeholders to improve educational systems and achieve gender equality, which is in line with India’s sustainable development goals. The study reinforces the point that education is not just a ladder for individual upliftment, but a key promoter of collective advancement for society at large, creating an even playing field for women from every nook and corner of the country.